Mediation on Industrial Relation Dispute and Its Relation With Relative Authority in The Legal Proceedings Process - Sarira, Iron (Humaniora, 2016)
Industrial Relations or Employment in the Indonesia legal system is based on Law No 13 of 2003 on Employment, and the Law No 2 of 2004 concerning Industrial Relations Dispute Settlement. The industrial relations are expected to be harmonious and give positive mutual engagement in the effort to support the development of Indonesian society and to improve the welfare of the Indonesian people, especially the workers or the labors. The desired goal is still far from the expectations if seeing the practice of industrial relations. The aim of the research was to get a better understanding of the practice and theory following the laws which regulated the procedures of employment as well as technical aspects. The research method applied was library research. There was some positive law approaches related to this research, which consisted of several rules as the normative law, such as Law No 2 of 2004, Act Number 30 of 1999, and PERMA No 1 of 2008. The research finds that the dispute of industrial relations as mentioned in Article 4 PERMA No 1 of 2008, Article 8 of Law No 2 of 2004, and Article 136 paragraph (2) of Act 13 of 2003. It explains and requires the mediation process before going into the courts of first instance (in this case is the Industrial Relations Court). The mediation process is led by a mediator who has the authority to conduct industrial relations dispute resolution processes in their jurisdiction. Industrial relations mediator does not have the authority to process the industrial relations dispute if the case territory is not located within its jurisdiction. As for, the relative authority of this provide an understanding that mediator aims to resolve disputes in industrial relations must apply the principle of locus delictus as a manifestation of its authority under the jurisdiction of the law.